Performance Analysis Rim Driven Propeller as a Propulsor using Open Water Test - Agoes Santoso; Irfan Syarif Arief; Anggara Tio Kurniawan (International Journal of Marine Engineering Innovation and Research, 2017)
The use of duct in propeller is one of the breakthrough in the development of the propeller. Ducting not only claimed to be increasing efficiency of the propeller, but also capable to protect the propeller from impact therefore propeller lifespan is longer. From that idea then RDP is created. RDP propeller blade are designed to be fix at their housing called Rim, in the other word, the driving force came from it’s rim. On current RDP blade used is non-conventional blade. This thesis will discuss about design analysis of Kaplan Propeller Kaplan Ka-70 that modified on it’s thickness distribution. On this thesis data that is varied is motor load. Simulation using Open Water Test. The result, highest value of KT and KQ occur on 30% motor load and highest efficiency is 18,338% achieved on 260 Rpm.